Outcomes in patients with smaller body surface area after HeartMate 3 left ventricular assist device implantation. Issue 3 (21st September 2021) - Molina, Ezequiel J.; Ahmed, Sara; Jain, Amiti; Lam, Phillip H.; Rao, Sriram; Hockstein, Michael; Kadakkal, Ajay; Hofmeyer, Mark; Rodrigo, Maria E.; Najjar, Samer S.; Sheikh, Farooq H.
Abstract: Background: Due to anatomic and physiologic concerns, prior generations of the left ventricular assist devices (LVAD) have frequently been denied to patients with small body size. However, outcomes in patients with small body surface area (BSA) following HeartMate 3 (HM3) LVAD implantation remain relatively unknown. Methods: A cohort of 220 patients implanted at a single center was divided into two groups: BSA ≤1.8 m 2 (small BSA, n = 37) and BSA >1.8 m 2 (large BSA, n = 183). We investigated baseline characteristics and clinical outcomes including survival and incidence of adverse events. Results: Small BSA patients were older (60 vs. 57 years), more likely female (60% vs. 20%), had a lower body mass index (24 vs. 32 kg/m 2 ), lower incidence of diabetes (32% vs. 51%), history of stroke (5% vs. 19%), and left ventricular thrombus (0% vs. 11%). They had smaller left ventricular end diastolic diameter (64.8 vs. 69.3 mm). Pump speed and pump flows at discharge were lower in the small BSA group. Survival at 1 year and 2 years was 86% versus 87% and 86% versus 79% for small versus large BSA groups ( p = 0.408), respectively. The rates of adverse events were similar between groups and there were no cases of confirmed pump thrombosis. The incidence of readmissions for low flow alarms was higher in the small BSA group (0.55 vs. 0.24 EPPY). Conclusions: These findings demonstrate comparable outcomes in patients with small body size and suggest that this parameter should not be an exclusion criterion on patients who are otherwise candidates for HM3 LVAD implantation. Abstract : Smaller body size patients were older, more likely female, had lower incidence of diabetes, had a smaller left ventricular end diastolic diameter, and had lower pump speeds and pump flows at discharge. Survival at 1 and 2‐years and incidence of adverse events was similar, whereas readmissions due to low flow alarms were higher in smaller patients. Small body size should not be an exclusion criterion for HeartMate 3 LVAD implantation.